Rebuilding legitimacy in a post-truth age - Watts, Duncan J.; Rothschild, David (Medium, 2017)
The current state of public and political discourse is in disarray. Politicians lie with impunity. Traditional news organizations amplify fact-free assertions, while outright fake news stories circulate on social media. Public trust in the media, science, and expert opinion has fallen, while segregation into like-minded communities has risen. Millions of citizens blame their economic circumstances on caricatures like “elites” rather than on specific economic forces and policies. Enormously complex subjects like mitigating climate change, or balancing economic growth and inequality, are reduced to slogans. Magical thinking (e.g., that millions of manufacturing jobs can be created by imposing trade restrictions; that everyone can have affordable, high quality, healthcare without individual mandates or subsidies; that vaccines cause autism) has proliferated.